Factors Influencing the Risk of Reumatoid Arthritis in Patients at Baiturrahman Health Center - Lestari, Yani (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Rheumatoid arthritis or rheumatism is an inflammation of the connective tissue, especially affecting the skeletal muscles, bones, ligaments, tendons and joints in men and women of all ages. Risk factors for rheumatoid arthritis are caused by infection, occupation, food, genetics, age and psychological factors. Rheumatoid arthritis can cause muscle changes, so that its function can decrease if the muscles in the patient's part are not trained to activate muscle function. This type of research is Analytical with a Cross Sectional research design. The aim is to analyze the factors that influence the risk of developing rheumatoid arthritis in patients at the Baiturrahman Health Center. The study population consisted of 314 patients with rheumatoid arthritis. The sample of this research was 76 people who were taken by accidental sampling. The data collected is primary data obtained by direct interviews using questionnaires. Data were analyzed in distribution and frequency tables. The results of the study showed that the majority of risk factors were infection (77.6%), the majority of occupational factors were at risk of (85.5%), the majority of food factors were at risk of (56.6%), the majority of genetic factors were at risk of (90.8%), and psychological factors (100%) are at risk. In conclusion, the dominant risk factor for rheumatoid arthritis in patients is psychological factors. Rheumatoid arthritis patients are expected to reduce psychological burdens such as stress and anxiety which easily tire the body, to avoid consuming foods that contain purines, and in doing daily work so as not to put excessive pressure on joints and muscles. It is hoped that Baiturrahman Health Center staff should provide counseling to rheumatoid arthritis patients on how to reduce the psychological burden, types of food consumed, and jobs that can put excessive pressure on joints and muscles.